Exploring Internet Addiction in Students of the University of Tehran Using a Grounded Theory Approach - Fatemeh Alavi asil; Khadijeh Abolmaali Hosseini; Simin Bashardust (Kerman University of Medical Sciences, 2022)
Background: The increasing growth and adverse effects of internet addiction have made this disorder a factor underlying all behavioral addictions. The present study aimed to explain the process of internet addiction in students of the University of Tehran.Methods: This qualitative study was conducted based on the grounded theory which is an exploratory research method. The research population included students with internet addiction at the University of Tehran in the academic year 2019-2020. Using purposive sampling and theoretical saturation criteria, 15 students (5 males and 10 females) were selected as the participants in the study. The data were collected through structured interviews with the students.Results: Based on the analysis of the data from the interviews, the factors effective in the formation of internet addiction were classified into 43 primary themes and 14 subcategories that were summarized into 5 main categories including individual factors, family factors, social factors, educational factors, and features of the internet.Conclusion: Students' internet addiction can be attributed to personality factors, psychological disorders, and family factors. The findings of this study provided a clear picture of internet addiction. The results of this study can be useful for psychologists and therapists to better understand this phenomenon and plan strategies for the prevention and treatment of internet addiction.